Economic Impact of Early Detection and Early Intervention of Psychosis - R. Valmaggia, Lucia; K McGuire, Philip; Fusar-Poli, Paolo; Howes, Oliver; McCrone, Paul (Current Pharmaceutical Design, 2012)
Background: Whilst there is a growing body of evidence relating to the effectiveness of early detection and early intervention services there have been relatively few studies which have provided information on whether they are cost-effective. Aim: The aim of this paper is to review the cost-effectiveness evidence for early detection and early intervention in psychosis. Methods: Full economic evaluations, cost studies, and studies which do not report costs but do provide important resource use information were included in the review. Results: All cost effectiveness analysis to date suggest that it is possible to offer help early in the development of psychosis in a cost effective manner. Conclusions: The potential longer term economic benefits of early detection and early intervention are required.
Keywords: relapse rate